The role of ageing and oxidative stress in intervertebral disc degeneration - Wen, Pengfei; Zheng, Bolong; Zhang, Binfei; Ma, Tao; Hao, Linjie; Zhang, Yumin (Frontiers in Molecular Biosciences, 2022)
Intervertebral disc degeneration (IDD) is the primary cause of intervertebral disc disease. With the increased ageing of society, an increasing number of patients are plagued by intervertebral disc disease. Ageing not only accelerates the decreased vitality and functional loss of intervertebral disc cells but also increases intracellular oxidative stress. Moreover, the speed of intervertebral disc ageing is also linked to high levels of reactive oxygen species (ROS) production. Not only is the production of ROS increased in ageing intervertebral disc cells, but antioxidant levels in degenerative intervertebral discs also decrease. In addition to the intervertebral disc, the structural components of the intervertebral disc matrix are vulnerable to oxidative damage. After chronic mitochondrial dysfunction, ROS can be produced in large quantities, while autophagy can eliminate these impaired mitochondria to reduce the production of ROS. Oxidative stress has a marked impact on the occurrence of IDD. In the future, IDD treatment is aiming to improve oxidative stress by regulating the redox balance in intervertebral disc cells. In summary, ageing and oxidative stress promote the degeneration of IVD, but further basic and clinical trials are needed to determine how to treat oxidative stress. At present, although there are many in-depth studies on the relationship between oxidative stress and degeneration of intervertebral disc cells, the specific mechanism has not been elucidated. In this paper, the main causes of intervertebral disc diseases are studied and summarized, and the impact of oxidative stress on intervertebral disc degeneration is studied.